The effects of seismic operations in UK waters: analysis of Marine Mammal Observer data - Stone, Carolyn; Hall, Karen; Mendes, Sonia; Tasker, Mark (J. Cetacean Res. Manage., 2023)
Sixteen years of information from observers on board seismic survey vessels in UK and adjacent waters have demonstrated the varied responses of marine mammals to seismic surveys. Most species showed some response to firing with ‘large arrays’ (airgun volume 500 cubic inches or more), but responses were less evident when "small arrays" (less than 500 cubic inches) were active. Several species/species groups responded proactively to the soft start procedure (where the level of firing is increased gradually) indicating that this can be an effective mitigation measure in reducing the risk of physiological damage. Despite the challenge in assigning ecological significance to the varied observed effects, the analyses in this study confirm that marine mammals are sensitive to noise from seismic surveys and therefore mitigation measures should continue to be applied to all seismic operations and such measures should cover all species.